2007
DOI: 10.1016/j.febslet.2007.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharide recognition and binding to the carbohydrate binding module of AMP‐activated protein kinase

Abstract: The AMP-activated protein kinase (AMPK) contains a carbohydrate-binding module (b1-CBM) that is conserved from yeast to mammals. b1-CBM has been shown to localize AMPK to glycogen in intact cells and in vitro. Here we use Nuclear Magnetic Resonance spectroscopy to investigate oligosaccharide binding to 15 N labelled b1-CBM. We find that b1-CBM shows greatest affinity to carbohydrates of greater than five glucose units joined via a,1 fi 4 glycosidic linkages with a single, but not multiple, glucose units in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 24 publications
(31 reference statements)
4
28
0
Order By: Relevance
“…They show addition of glycogen to rat liver AMPK is inhibitory, and when recombinant AMPK is expressed in CCL13 cells, this inhibition is dependent on the presence of CBM. In agreement with Koay et al (256), they provide evidence that inhibition is mediated by the ␣136 linkages and require the key sugar binding Trp residues in the CBM. Isomaltose, but not maltose, inhibited rat liver AMPK with a half-maximal effect at 16 mM (317).…”
Section: E Ampk Interaction With Glycogensupporting
confidence: 75%
See 2 more Smart Citations
“…They show addition of glycogen to rat liver AMPK is inhibitory, and when recombinant AMPK is expressed in CCL13 cells, this inhibition is dependent on the presence of CBM. In agreement with Koay et al (256), they provide evidence that inhibition is mediated by the ␣136 linkages and require the key sugar binding Trp residues in the CBM. Isomaltose, but not maltose, inhibited rat liver AMPK with a half-maximal effect at 16 mM (317).…”
Section: E Ampk Interaction With Glycogensupporting
confidence: 75%
“…Another feature of the structure is the extension of the side chain of Leu-146 through the core of the bound cyclodextrin. Solution studies using NMR have also been reported, showing that the CBM binds maltohexose and maltohepulose with K D values Ͻ1 mM while shorter oligosaccharides bind substantially less strongly (256). The NMR results also showed chemical shifts in all the key sugar binding residues in the presence of maltoheptulose with the exception of Trp-100.…”
Section: E Ampk Interaction With Glycogenmentioning
confidence: 71%
See 1 more Smart Citation
“…Most b subunits also contain carbohydrate-binding modules (CBMs), noncatalytic domains also found in enzymes (in both prokaryotes and eukaryotes) that metabolize starch and glycogen (Machovic and Janecek 2006). The CBMs cause mammalian AMPK to bind to glycogen in intact cells (Hudson et al 2003;Polekhina et al 2003Polekhina et al , 2005Koay et al 2007;Bendayan et al 2009). The physiological role of this remains uncertain, although one function may be to localize AMPK with downstream targets also bound to glycogen, such as glycogen synthase (Carling and Hardie 1989;Jorgensen et al 2004).…”
Section: Role Of Ampk Orthologs In Nonmammalian Eukaryotesmentioning
confidence: 99%
“…Previously, CBMs were thought to be motifs that are functionally independent from the catalytic domains located distal to the active sites, and it has been proposed that they enhance the interaction between the carbohydrate substrate and protein (52)(53)(54)(55). For many amylolytic enzymes, CBMs were reportedly involved in starch hydrolysis by disrupting the starch granule structure, which allowed for a concentration of catalytic domains on the surface and carbohydrate starch hydrolysis by proximity (56 -59).…”
Section: Discussionmentioning
confidence: 99%